Prognostic factors of leg amputation in patients with vascular injury: a systematic review - Rerkasem K. (2014)
Individual studies on the prognostic factors of leg amputation, due to vascular injury, have been small, and they have produced conflicting results. Reliable data are necessary so that surgery can be targeted more effectively. The authors carried out a systematic review from 1990 to 2002 to identify the high risk of patients to amputation. Meta-analysis was carried out. The authors found that patients with preoperative hypotension, popliteal artery injury, and associated bone and nerve injury had a significantly higher risk of leg amputation than those without these risk factors. Also, patients with postoperative infection had a higher chance of amputation than those without infection. This information is essential for an appropriate evaluation and the treatment of such patients.